Bilateral Insufficiency Fracture of the Pelvis Following THA: A Case Report - Shinya Hayashi; Takayuki Nishiyama; Takaaki Fujishiro; Shingo Hashimoto; Masahiro Kurosaka (Case Reports in Medicine)
Insufficiency fracture is of the stress fractures and is caused by repetitive stress on fragile bone. Insufficiency fractures of pubic rami are rare occurrences in association with total hip arthroplasty (THA). Postoperative stress fractures occur due to increase of patients activity following years of disability. The physician should consider the possibility of a pelvic insufficiency fracture in patients with RA after THA, if the patients present with groin pain. We demonstrate here the first case of bilateral insufficiency fracture of pubic rami and iliac bone following THA.